2009
DOI: 10.1021/jp8090304
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Laccase on Nanoporous Gold: Comparative Studies on the Immobilization Strategies and the Particle Size Effects

Abstract: Nanoporous gold (NPG), prepared simply by dealloying Ag from Au/Ag alloy, was used in the present study as a carrier for laccase immobilization. Three immobilization strategies, i.e., physical adsorption, electrostatic attraction, and covalent coupling, were used to immobilize laccase on NPG. A detailed comparison among the three strategies was made in light of the loading, the specific activity, and the leakage of laccase. The present results indicated that the physical adsorption strategy was the best one fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 26 publications
5
99
1
2
Order By: Relevance
“…On changing the immobilization conditions to vacuum deposition of the ThLc solution on a bare, vacuum dried nanoporous gold electrode, followed by covering the electrode with a P017-epoxy cap, significantly higher currents of 7 µA (Fig 1B) were obtained. As reported previously, the linkages formed by chemisorption of the NH 2 groups of the lysine residues of ThLc on nanoporous gold are as strong as those for -SH groups on gold [32]. However, a P017-epoxy cap was also applied [33] to prevent any possible leaching of the enzyme from the gold surface.…”
Section: Resultsmentioning
confidence: 92%
“…On changing the immobilization conditions to vacuum deposition of the ThLc solution on a bare, vacuum dried nanoporous gold electrode, followed by covering the electrode with a P017-epoxy cap, significantly higher currents of 7 µA (Fig 1B) were obtained. As reported previously, the linkages formed by chemisorption of the NH 2 groups of the lysine residues of ThLc on nanoporous gold are as strong as those for -SH groups on gold [32]. However, a P017-epoxy cap was also applied [33] to prevent any possible leaching of the enzyme from the gold surface.…”
Section: Resultsmentioning
confidence: 92%
“…These SAMs can act as simple modifiers [68] or be used as linkers to attach various molecules to its surface such as proteins, enzymes, antibodies, or photosystem I [65,66,90,[106][107][108][109]. Because of the very high surface areas of nanoporous gold, a significantly larger amount of the modifier can be immobilized on its surface relative to a planar gold electrode.…”
Section: Specific Features Of Nanoporous Goldmentioning
confidence: 99%
“…A schematic of the immobilization of lipase onto nanoporous gold is shown in Figure 9 [139]. Nanoporous gold has already been shown to be a good support for the immobilization of a wide variety of proteins/enzymes including laccase [106,108,134,138], glucose Figure 9: A schematic of the immobilization of lipase onto nanoporous gold [139]. Reprinted from [139].…”
Section: Dna Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all these methods, adsorption is relatively simple and less expensive, so it may have a higher commercial potential than the other methodologies. Some studies have demonstrated that adsorption is preferable to other techniques for the immobilization of some particular laccases [10]. Recently, metal-based supports have been receiving emerging attention for metal-chelated enzyme adsorption [9].…”
Section: Introductionmentioning
confidence: 99%